Epistemic and Chronological Criticism in the Safīnah Kallā Saya‘lamūn Exegesis Surah Ar-Rūm [30]:1–5 - Masgun Arifin; Ahmad Nabilul Maram (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2026)
This discourse examines the Safīnah Kallā Saya‘lamūn exegesis, which employs historical analogies to demonstrate the relevance of the historical content in the Qur’an; however, the criteria for testing these claims against empirical history remain underdeveloped. This study proposes a “Chronological-Epistemic Evaluation” model to critique the use of historical analogies in Indonesian exegetical works, particularly the Tafsir Safīnah Kallā Saya‘lamūn, which interprets Surah Ar-Rūm [30]:1–5 by claiming a date correspondence (17 Ramadan/August 17) and stating that a discrepancy of one or two days is permissible across all calendars. Through qualitative research, this study employs an astronomical algorithm for Hijri-Gregorian conversion to verify the claim of a direct temporal correspondence between the Roman victory (7th century) and Indonesian Independence (1945). The research findings indicate that the text operates through a "mediating authority" structure, projecting a nationalist narrative onto the Qur’anic text to achieve "symbolic truth". However, a rigorous chronological analysis proves that the claim of date correspondence is astronomically impossible due to the stability of the Gregorian calendar and the shifting lunar cycle. This study concludes that the text commits a category error by conflating metaphor (majāz) with empirical fact (haqīqah), thereby threatening scholarly integrity. Consequently, this research recommends that contemporary mufassirs adopt a "double validation" protocol balancing contextual relevance with strict empirical audits before publishing historical claims and advises readers to critically approach such historical analogies as symbolic pedagogy rather than literal historiography, thereby reinstating the principle of academic caution (iḥtiyāṭ).